Post-traumatic stress disorder among Iranian women with genital mutilation: a cross-sectional study - Mahsa Abdollahzadeh; Roghaiyeh Nourizadeh; Niloufar Sattarzadeh Jahdi (BMC, 2023)
Abstract Background The conflicting evidence on the relationship between female genital mutilation/ cutting (FGM/C) and post-traumatic stress disorder (PTSD) may be due to the differences in the prevalence and type of FGM/C in different societies. The present study aimed to assess the prevalence and severity of PTSD and its associated factors among Iranian women with genital mutilation. Methods This cross-sectional study was performed on 155 women with genital mutilation aged 18-45 years referred to the health centers in Mahabad, located in west of Iran from October 2020 to April 2021. The participants were selected using convenience sampling method. After obtaining the informed consent form from the participants, the first researcher in the presence of a gynecologist determined the type of genital mutilation through the gynecological examination. The data were collected using demographic and obstetric characteristics and post-traumatic stress disorder checklist (PCL5) and analyzed using SPSS21 software. Further, independent t-test, ANOVA, Pearson correlation coefficient, and multivariate linear regression were used. Result All 155 women (100%) had type 1 genital mutilation. Six women (3.9%) had PTSD. The mean (SD) score of the PTSD symptoms among the women was 27.73 (6.79) in the attainable score of 0-80. The age at FGM/C, level of education, and type of residence were considered as the predictors of the severity of the symptoms of PTSD, as explaining 48.1% of the variance. Conclusion and recommendation In the present study, the prevalence and severity of PTSD among the participants were relatively low, which may be due to convenience sampling method used in the study, the limited injury in genitalia, and the social acceptance of the practice. The results indicated that the severity of the PTSD symptoms enhanced by increasing age at FGM/C and decreasing socio-economic levels. It is recommended to conduct the similar studies among women with other types of FGM/C.